MENINGKATKAN KETERAMPILAN MENULIS TEKS NEGOSIASI MELALUI MODEL CIRC PADA SISWA FASE E DI SEKOLAH PENGGERAK SMAN 3 PADANG - Yasni Ustazah Fadly; Refa Lina Tiawati R; Ricci Gemarni Tatalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low ability to understand the structure and linguistic rules of writing negotiation texts. Students perceive writing as a rather boring subject. The objective of this study is to describe the effect of the Cooperative Integrated Reading and Composition (CIRC) model on the negotiation text writing skills of Phase E students at SMA Negeri 3 Padang. This quantitative research used an experimental method with a One Group Pretest-Postest Design. The population was all Phase E students at SMA Negeri 3 Padang. The sampling technique used was purposive sampling. The sample was grade E1 students. The instrument used in this study was a performance test. The data were scores from the negotiation text writing performance test before and after using the Cooperative Integrated Reading and Composition (CIRC) model. The results of this study. First, the negotiation text writing skills before using the Cooperative Integrated Reading and Composition (CIRC) model of phase E students of SMA Negeri 3 Padang were at a mastery level of 66-75% with more than sufficient qualifications by obtaining an average of 70.60. The weaknesses of students before using the Cooperative Integrated Reading and Composition (CIRC) model were in the text structure indicators and language rules of the negotiation text. Second, the negotiation text writing skills after using the Cooperative Integrated Reading and Composition (CIRC) model of Phase E students of SMA Negeri 3 Padang were at a mastery level of 86-95% with very good qualifications by obtaining an average value of 87.27. In the application of the Cooperative Integrated Reading and Composition (CIRC) model, the mastery of the structure indicators and language rules of the negotiation text was good. Third, the use of negotiation texts had a significant influence of 95% with dk-n-1 because < (95.1> 1.70). The Cooperative Integrated Reading and Composition (CIRC) model significantly influences negotiation text writing skills because the Cooperative Integrated Reading and Composition (CIRC) model is a cooperative learning model that involves students in small groups to learn to read and write in an integrated manner.